BENTUK PENYELESAIAN SERTIFIKAT TUMPANG TINDIH HAK MILIK ATAS TANAH DI TANGANI OLEH SWA LAW OFFICE - Mahadewi, Kadek Julia; Adinda, I Gusti Ayu Sri (Belom Bahadat, 2024)
He existence of land in Indonesia is a blessing that can be found in Indonesia with all the benefits available in it. The regulations are regulated in article 33 of the 1945 Constitution, UUPA and the PP on Land Registration. Land problems in the community can never be avoided. One of the problems that arise is overlapping certificates in the community, this can occur in the form of errors in orifice or duplicate certificates. Problems that arise What are the causes of overlapping certificates and how does the SWA Law Office handle these cases? This journal's method is empirical research and uses a case and law approach, the analysis is descriptive. The reason for the overlapping certificates is deliberate mention of the location, errors in administration. Completion of overlapping certificates is carried out with complaints regarding problems occurring.